Development of Android-based Electronic Flipbook (E-Book) with Augmented Reality Technology in Green Business Courses - Siahaan, Sabda Dian Nurani; Ruslan, Dede; Fikri, Miftah El; Saragih, Lenti Susanna (Universitas Pendidikan Mandalika (UNDIKMA), 2024)
This research aimed to develop an interactive Android e-book using Augmented Reality (AR) to enhance student learning outcomes of Green Business courses. The e-book included both offline and online resources and utilized AR to provide 3D visuals for a more engaging learning experience. The method used was Research and Development (R&D) with the Plomp Model. This model consists of five stages namely Preliminary Investigation ; Design ; Realization / Construction ; Test, Evaluation and Revision ; and Implementation. The data analysis technique is an Effectiveness Test using SmartPLS4 software. The results showed that the Green Business e-book effectively improved students' learning outcomes. This research indicates that visually-based e-books can be an effective tool for enhancing student learning outcomes. Educational institutions should consider developing more digital learning materials, especially those related to topics such as Green Business.